Assessment of Potential Drug–Drug Interactions in an Oncology Unit of a Tertiary Care Teaching Hospital - Vayalil, Ramya Kuzhikattu; Shetty, K Jayarama; Mateti, Uday Venkat (Indian Journal of Medical and Paediatric Oncology, 2018)
Context: Drug interactions are more common in cancer patients because they consume several medicines such as hormonal substances, anticancer drugs, and adjuvant drugs to treat comorbidities. Objectives: To assess the pattern of potential drug–drug interactions (pDDIs) in an oncology unit of a tertiary care teaching hospital. Materials and Methods: A prospective observational study was carried out for 8 months (August 2016 to March 2017). Data on drugs were collected by reviewing the patients’ medical records. The drug interactions fact software version such as Micromedex electronic database system, drugs.com interaction checker, and Medscape multidrug interaction checker tool were used to identify and analyze the pattern of pDDIs. Results: A total of 180 patients were enrolled during the study period. Among them, 152 study patients had 84.44% of pDDIs. Male predominance (64.4%) was noted over female (35.6%). According to the severity of classification of pDDIs, majority of them were moderate (63.1%) followed by major (26.1%) and minor (10.1%) interactions. The interactions that potentially cause QT interval prolongation and irregular heartbeat were the common outcomes of pDDIs. Conclusions: The incidence of pDDIs among cancer patients was 84.44%. The most common interacting drug pair in the study population was found to be dexamethasone + aprepitant [41 (26.9%)] followed by cisplatin + dexamethasone [32 (21.05%)] and other interacting pairs. To avoid harmful effects, screening of pDDIs should take place before administering the therapy.
Keywords: Antineoplastic agents; chemotherapy; drug interactions